Simulating Performance of a Dual Angle Particle Monitor for Atmospheric Particulate Matter - Charles D. Litton; Aranya Venkatesh; Jill Andersen; Dömötör Gulyás; Sara Longo; Chris Bartley; Illah Nourbakhsh (Aerosol and Air Quality Research)
Abstract Recent literature suggests that particle toxicity increases with decreasing particle diameter and increasing total particle surface area. Most inexpensive particle monitors are based upon light scattering and tend to lose sensitivity for particles with diameters less than about 0.3–0.35 µm. This raises the question of whether the measurement of PM2.5 “misses” the potential impact of very small particles (e.g., below 0.3 µm) due to lack of sensitivity and/or the low mass concentrations that these particles contribute to the total PM2.5. On the other hand, measuring only ultrafine particles (e.g., below 0.1 µm) would exclude significant numbers of still very small particles. The focus of simulating a novel particle monitor in this study, is to address limitations in current inexpensive particle monitors, and to realize a particle monitor that may be more relevant to adverse health outcomes by measuring both PM0.3 and PM2.5. The monitor uses optical scattering techniques, measuring light scattering by the particles at two forward angles, to determine PM0.3 and PM2.5. Experimental data from particle monitor prototypes that were developed show good agreement with simulation results. Such a monitor, that is low-cost and easy to use, can provide information directly to the users so that they can be driven to action. In particular, low-income communities that are often impacted by poor air quality will be able to more affordably determine real-time ambient conditions and drive positive change by helping to identify pollution sources and appropriate mitigation measures.